Application of Jigsaw Type Cooperative Learning Model to Improving the Physical Exercise Students Volleyball at Junior High School 1 Sajoanging - Gatot Jariono; Fahmy Fachrezzy; Haris Nugroho (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study was to determine the improvement of learning outcomes squat-style long jump through the Jigsaw cooperative learning model for students who took extracurricular volleyball games at Junior High School 1 Sajoanging, Wajo Regency, South Sulawesi Province. The approach in this research is a quantitative descriptive approach with quasi research type. The implementation of this research is focused on two variables, namely the Jigsaw cooperative learning model and the squat style long jump learning outcomes. This research was conducted at Junior High School 1 Sajoanging, Wajo Regency, South Sulawesi Province. The research subjects were 25 grade VII students. The data collection techniques used were observation, tests and documentation. The data analysis technique used is qualitative and quantitative descriptions. Based on the results of the study, it can be concluded that the learning process using the Jigsaw cooperative learning model has been proven to be effective in improving the learning outcomes of the squat style long jump of students who take extracurricular volleyball games at Junior High School 1 Sajoanging, Wajo Regency, South Sulawesi Province.